Peranan Plasmafaresis pada Keracunan Bisa Ular Tipe Neurotoksik - Agus Sumedi (Jurnal Penelitian Keperawatan Medik, 2018)
Female 19-year old with severe general neuroparalytic, admitted in intensive care unit with respiratory failure. He suffer from snake bite during night sleeping 2 hours before arrived in emergency unit of RSCM hospital. In early after snake bite, patient complained nausea, dizziness, limb parasthesia then felt uncomfortable eyesight. During observation in emergency unit anti venom serum (AVS) was given immediately 2 vial (10 ml) in 250 ml normal saline for an hour and then 2 vials in 250 normal saline in 3 hours ,but about 3 hours post bitten, patient suffer from ptosis, opthalmoplegia and quadriplegia, respiratory shortness followed by respiratory arrest. We diagnosed it as respiratory failure and neuromotoric paralytic ec. snake venom intoxication. After intubation and second dose AVS, patient moved to ICU for mechanical ventilation support and further treatment. We did CVVHDF for three days, AVS shcedulles 6 vials in 24 hours for 6 days. Until 7 days stay in ICU there were neuroparalytic improvement but not progressively and patient still on ventilator. Pasmapharesis then performed at 8thand 12th day in ICU. Weaning process going on smoothly and patient extubated at 14th day. Patient discharged from ICU at 16th day with fully aware, normal heart rate and blood pressureand score muscle strength is 4 until 5. We concluded that the neurotoxin venom in this case destructed vesicles presynaptic of nerve terminalmake resistant to AVS and neostigmin. We suspect this patient was exposedto high dose and more toxic venom where released continuously from bite site tissue or lymph circulation to blood and threaten recovery process. Plasmapharesis improve neuroparalytic and sympathetic overactivity significantlyand decrease lenght of stay in ICU.